PEMBERDAYAAN NELAYAN TRADISIONAL MELALUI MEDIA KOMUNIKASI DAN TIK DI PANTAI SELATAN JAWA - Arifianto, Somo; Rusadi, Udi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
The poverty of traditional fishermen on the south beach of Java has been going on across the generations both culturally and structurally. They live oppressed by the middlemen and owners of capital, so it needs to be empowered through integrated training of the use of communication media and ICT. The focus of this research is to describe and identify the characters of communication media and ICT which are needed by traditional fishermen when accessing information. The concept of empowerment refers to the theory of âsocial construction of technologyâ, which says that the communication media and ICT which are successfully used for empowerment in other sectors, can also be used in traditional fishermen according to their needs. This intertwined case study with qualitative approach, took place in five fishing villages on the south beach of Java, that are Pelabuhan Ratu, Pangandaran, Parangtritis, Munjungan and Muncar. This study aims to describe and identify the construction of communication media and ICT characters adapted to the social and cultural values, as well as social and cultural design of media and ICT, according to the needs of traditional fishermen. The results show that the communication media and ICT which have been identified and utilized by traditional fishermen to access information according to their needs such as face-to-face media, nature signs, handy talky, phone, radio and tv community, GPS and fishfinder. Some communication media and ICT can be used as basic material of tutorials for traditional fisher empowering models through training or workshop at research sites in the future